2008
DOI: 10.3748/wjg.14.3763
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic complete response confirmed by surgical resection for liver metastases of gastrointestinal stromal tumor after treatment with imatinib mesylate

Abstract: A 39-year-old male underwent distal gastrectomy for a high grade gastrointestinal stromal tumor (GIST). Computed tomography (CT) and magnetic resonance imaging (MRI) 107 mo after the operation, revealed a cystic mass (14 cm in diameter) and a solid mass (9 cm in diameter) in the right and left lobes of the liver, respectively. A biopsy specimen of the solid mass showed a liver metastasis of GIST. The patient received imatinib mesylate (IM) treatment, 400 mg/day orally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Similarly, Suzuki et al reported a case of pCR in GIST with imatinib that did not correlate with clinical or radiological response. This result was documented in a metastatic GIST that was subjected to hepatectomy for cystic lesions in both hepatic lobes [15]. In a series of 159 metastatic GISTs, 38 patients had a partial response with imatinib and underwent an operation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, Suzuki et al reported a case of pCR in GIST with imatinib that did not correlate with clinical or radiological response. This result was documented in a metastatic GIST that was subjected to hepatectomy for cystic lesions in both hepatic lobes [15]. In a series of 159 metastatic GISTs, 38 patients had a partial response with imatinib and underwent an operation.…”
Section: Discussionmentioning
confidence: 92%
“…Despite the long period of treatment until surgery (15 months), our patient did not develop such resistance. Other series have reported treatment durations of up to 35 months before surgery [15]. Another issue in GIST treatment is the predictive value of conventional imaging studies, such as computed tomography scan (TC), in evaluating the tumor response to imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 A summary of the morphological findings of metastatic GIST after Gleevec treatment is shown in Table 1. [2][3][4][5][6][7][8] Gleevec-treated hepatic metastatic lesions show a variety of histological findings. Pyknotic nuclei in an eosinophilic myxoid background with a decrease in the density of the tumor cells, myxoid degeneration, and scarring have been documented.…”
Section: Discussionmentioning
confidence: 99%
“…2 The morphological findings such as cystic changes, hemorrhage, myxoid degeneration, or a decrease in the number of tumor cells have been demonstrated in metastatic GISTs after Gleevec treatment. [2][3][4][5][6][7][8] However, the morphological features attributed to Gleevec ingestion have not been well characterized. Metastatic GISTs after Gleevec treatment mimic reactive lesions, epithelioid or spindle cell tumors.…”
mentioning
confidence: 99%
“…-On one hand, there are no cures with only medical treatment for GISTs; long-term survival in advanced disease only results from surgical resection, and pathological study nearly always shows persistent viable cells and persistent c-kit signalling in resection specimens of apparent complete response cases after imatinib treatment [32, 93,94].…”
Section: Sunitinibmentioning
confidence: 99%